Incoherent interlayer electron hopping as a possible reason for enhanced magnetic quantum oscillations in the mixed state of a layered organic superconductor - Gvozdikov, V.M.; Wosnitza, J. (Физика низких температур, 2006)
We present a theory which is able to explain enhanced magnetic quantum-oscillation
amplitudes in the superconducting state of a layered organic metal with incoherent electronic
transport across the layers. The incoherence acts through the deformation of the layer-stacking
factor which becomes complex and decreases the total scattering rate in the mixed state. This novel
mechanism restores the coherence by establishing a long-range order across the layers and can
compensate the usual decrease of the Dingle factor below the upper critical magnetic field caused
by the intralayer scattering.